Description of a new species of Platypalpus of the candicans - cursitans subgroup from the Peloponnesus, Greece (Diptera: Hybotidae, Tachydromiinae) - Grootaert, Patrick; Alexiou, Sotiris (ENTOMOLOGIA HELLENICA, 2020)
Platypalpus cylleneus sp. n. belonging to the subgroup of Platypalpus candicans and cursitans is described from Mt Killini in the Peloponnesus, Greece. A review and a key to the members of the subgroup, P. candicans (Fallén, 1815), P. cursitans (Fabricius, 1775), P. cylleneus sp. nov. and P. nigrimanus Strobl, 1880, is provided.